IMPLEMENTASI TRANSAKSI DIGITAL DALAM PERSPEKTIF FIQH MUAMALAH - Irsyad Kurniawan Widjanarko; Muhammad Bobby Hafidz; Nurlabibah Elsyia Jundiah; Erlina Salsa Anjani (Taksasila Edukasi Insani, 2025)
The development of information technology has led to a shift in the economic transaction system towards digital. This change brings convenience, but also challenges in maintaining the suitability of transactions with sharia principles in muamalah fiqh. This research aims to examine the implementation of digital transactions from the perspective of Islamic law. The method used is a literature study. The results of the analysis show the importance of the principles of justice, clarity of contracts, transparency, and the prohibition of usury, gharar, and maysir in digital transactions. Islamic financial institutions play a role in providing sharia-compliant digital services. The main challenges faced are the lack of public understanding and the security risks of digital transactions. The solution offered is continuous education and strengthening sharia-based regulations. With this approach, digital transactions can develop in line with Islamic values.Keywords : Digital Transactions, Fiqh of Muamalah, Islamic Finance, Islamic Law